IMF Survey : Volume 29, Issue 15. (IMF Survey; IMF Survey, 2000)
The leaders of the Group of Seven and Group of Eight countries held summit meetings in Okinawa, Japan, on July 21-23. Two statements were issued at the meetings: the first, on July 21, by the leaders of the Group of Seven countries, comprising Canada, France, Germany, Italy, Japan, the United Kingdom, and the United States; and the second, on July 23, by the leaders of the Group of Eight countries (Group of Seven plus Russia). Excerpts from the statement of the Group of Seven follow (see page 245 for an excerpt from the Group of Eight statement).